Natural variation of OsML1, a mitochondrial transcription termination factor, contributes to mesocotyl length variation in rice - Meng, Yun; Zhan, Junhui; Liu, Hongyan; Liu, Jindong; Wang, Yamei; Guo, Zhan; He, Sang; Nie, Lixiao; Kohli, Ajay; Ye, Guoyou (Wiley, 2023)
Mesocotyl length (ML) is a crucial factor in determining the establishment and yield of rice planted through dry direct seeding, a practice that is increasingly popular in rice production worldwide. ML is determined by the endogenous and external environments, and inherits as a complex trait. To date, only a few genes have been cloned, and the mechanisms underlying mesocotyl elongation remain largely unknown. Here, through a genome‐wide association study using sequenced germplasm, we reveal that natural allelic variations in a mitochondrial transcription termination factor, OsML1, predominantly determined the natural variation of ML in rice. Natural variants in the coding regions of OsML1 resulted in five major haplotypes with a clear differentiation between subspecies and subpopulations in cultivated rice. The much‐reduced genetic diversity of cultivated rice compared to the common wild rice suggested that OsML1 underwent selection during domestication. Transgenic experiments and molecular analysis demonstrated that OsML1 contributes to ML by influencing cell elongation primarily determined by H2O2 homeostasis. Overexpression of OsML1 promoted mesocotyl elongation and thus improved the emergence rate under deep direct seeding. Taken together, our results suggested that OsML1 is a key positive regulator of ML, and is useful in developing varieties for deep direct seeding by conventional and transgenic approaches.